Translating T. S. Eliot: an exercise of paraphrase - Kangussu, André Mendes (2019)
This article takes a T. S. Eliot’s poem, “Eyes that last I saw in tears”, as a translating exercise. The poem has a complex rhythmic structure and a complex system of phonetic repetitions. The reproduction of those effects in a translation demands more from the translator’s efforts to paraphrase the original, that is, to retell it in other words. Our main goal is to give visibility to the multiplicity of ways of re-elaborating the poetry in the original. We start by commenting the poem and the author’s poetics. After this we present a table that suggests a variety of sentences and words to paraphrase each verse, and, finally, we propose six translations that were based on this table.